2017
DOI: 10.4149/bll_2017_092
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes following minimal invasive versus conventional aortic valve replacement: a propensity match analysis

Abstract: INTRODUCTION: Minimal invasive aortic valve replacement has become a routine procedure. In this study, we compared the outcomes between conventional and minimal invasive aortic valve replacement via the partial upper sternotomy that were performed in our Institution. METHODS: The 5 year survival and postoperative outcomes of 34 patients that underwent isolated MIAVR between the years 2010-2013 were compared with the outcomes of 34 randomly selected patients that underwent conventional AVR, after propensity mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 32 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Two studies reported on pulmonary infection: MIVS was associated with a lower chance of infection, but this difference was not significant (OR 1.35; 95% CI [0.16, 11.30]; p = 0.78) ( 13 , 17 ). The incidence of postoperative pleural effusion was reported in 8 studies; this was not significantly different between the groups (OR 0.81; 95% CI [0.45, 1.45]; p = 0.47) ( 6 , 16 , 18 , 20 , 21 , 28 , 29 , 36 ). We also compared the incidence of prolonged ventilation time based on data pooled from 10 studies; there was no significant difference between the groups (OR 0.72; 95% CI [0.51, 1.01]; p = 0.06) ( 14 , 19 22 , 25 , 27 , 31 , 37 , 39 ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Two studies reported on pulmonary infection: MIVS was associated with a lower chance of infection, but this difference was not significant (OR 1.35; 95% CI [0.16, 11.30]; p = 0.78) ( 13 , 17 ). The incidence of postoperative pleural effusion was reported in 8 studies; this was not significantly different between the groups (OR 0.81; 95% CI [0.45, 1.45]; p = 0.47) ( 6 , 16 , 18 , 20 , 21 , 28 , 29 , 36 ). We also compared the incidence of prolonged ventilation time based on data pooled from 10 studies; there was no significant difference between the groups (OR 0.72; 95% CI [0.51, 1.01]; p = 0.06) ( 14 , 19 22 , 25 , 27 , 31 , 37 , 39 ).…”
Section: Resultsmentioning
confidence: 97%
“…A full sternotomy was performed from the sternal notch to the xiphoid process. The definitions of the postoperative outcomes mainly depend on the descriptions mentioned in the original articles ( 8 , 18 , 39 , 43 45 ). Besides postoperative pulmonary complications were defined as complications occurring in the postoperative period and producing clinical diseases, such as pneumonia, pleural effusion, pneumothorax, pulmonary infection, and respiratory insufficiency (defined as the need for reintubation or tracheostomy after initial extubation), and prolonged ventilation time, which was defined as mechanical ventilatory support requirement for more than 24 h. Pulmonary function tests, represented by FEV1, TLC, and FVC, were assessed based on a spirometry test 1 week after surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Minimally invasive approaches to AVR include either a partial median sternotomy (mini-sternotomy, AVR-st) or a right anterior thoracotomy (AVR-th) incision. Although a number of studies have compared clinical outcomes between minimally invasive and conventional aortic valve replacement (cAVR) [2][3][4][5][6], very limited data exist comparing AVR-st versus AVR-th. Therefore, we conducted an indirect meta-analysis to compare these minimally invasive approaches with each other and with conventional surgical AVR.…”
mentioning
confidence: 99%
“…Minimally invasive and endovascular procedures are reported to be safer than open heart surgery and to be associated with less pain, less bleeding, and a shorter recovery period [31]. However, recent studies revealed that surgical interventions are also very safe.…”
Section: Safety Of Surgical Avr In the Modern Eramentioning
confidence: 96%
“…Surgery of the aortic valve has become extraordinarily safe in the present era, even compared to minimally invasive AVR as well as TAVR [31][32][33][34].…”
Section: Safety Of Avr In the Modern Eramentioning
confidence: 99%